PATIENTS' CHRONOTYPE INFLUENCE IN TREATMENT EFFICIENCY OF PLACENTA CRYERXTRACT CHANGES IN MAXILLOFACIAL PHLEGMONS - K. Lokes; M. Pérez Sayáns; V. Lychman; D. Steblovskyi; I. Boiko; D. Avetikov (Проблеми екології та медицини)
Among acute odontogenic inflammatory diseases, a significant subset comprises purulent processes in soft tissues, including abscesses and phlegmons. Methods. The study encompassed 90 patients (both male and female) diagnosed with maxillofacial phlegmons, aged between 35 and 60 years. These patients were divided into three clinical groups, each comprising 30 individuals, further categorized into two subgroups based on circadian rhythms. Analyzing the obtained data, it can be asserted that the most significant changes in markers of lipid peroxidation in patients with superficial phlegmons of maxillofacial localization were experienced in both experimental groups when used against the background of treatment according to standard protocols of intravenous injections of the cryopreserved placenta without and in combination with local injection of the cryopreserved placenta as part of "Levomekol" ointment, in contrast to the control group. It was proved that the markers of lipid peroxidation underwent the most significant changes in both clinical groups compared to the control group, but the largest changes were visualized in the second clinical group. On the 5th day of treatment, SOD activity reliably increases by 15.7% in patients with the morning chronotype and 14.9% - with the evening chronotype. A significant decrease in erythrocyte catalase activity by 51.5% was noted in patients with the evening chronotype and 56.1% - with the morning chronotype. In the control group, significant changes were noted only in the late stages of treatment. The dependence of lipid peroxidation markers on the timing of surgical intervention on the patient's circadian rhythm was established, which is most clearly observed in the 2nd clinical group. Optimal healing of a purulent wound helps to reduce the duration of treatment, accelerate the rehabilitation of patients, and improve the formation of a postoperative scar. Conclusion. Thus, aligning the timing of surgical intervention for maxillofacial phlegmons with the patient's circadian rhythm, particularly when combined with intravenous injections and local application of placenta cryoextract alongside standard treatment, contributes to an optimal modulation of lipid peroxidation markers.